RELEVANSI MUATAN HISTORIS DAN NILAI PENDIDIKAN KARAKTER DALAM NOVEL SEJARAH RORO MENDUT VERSI Y. B. MANGUNWIYA DI ERA DIGITAL - Febri Kevin Aditya; Ismail Lutfi; Lutfiah Ayundasari (Universitas Negeri Malang, 2021)
The digital age is inevitable. The rapid influence of the digitization process has led to a deterioration of character values in students. Students' characters can be built through historical learning based on the search for meaning in the text of historical novels by exploring the educational value of the characters in them. This research aims to describe the value of character education in Roro Mendut historical novel version Y.B. Mangunwijaya and its relevance as reflective material to overcome various challenges of the digital age. This research is qualitative with Ferdinand de Saussure semiological analysis as an analytical technique. The results of this study showed the existence of historical content and found five main educational character values set by the Ministry of Education and Culture. The historical content and educational characters values found to have relevance to the modern life of the digital age. Relevance can be pursued as a historical learning material that builds the character of students. To be utilized in history learning in the classroom, special learning methods are required.